WINNING ON PURPOSE : THE UNBEATABLE STRATEGY OF LOVING CUSTOMERS - Reichheld, Frederick F.; Darnell, Darci; Burns, Maureen (Boston, Massachusetts : Harvard Business Review Press, 2021)
"Can your company win by embracing a higher purpose? The answer is a resounding yes-and this book tells you how. Few management ideas have spread so far and so wide as the Net Promoter System (NPS). Since its introduction two decades ago by author and customer loyalty guru Fred Reichheld, companies across the spectrum have adopted it-from industrial giants such as Mercedes-Benz and Cummins to Silicon Valley sweethearts such as Apple and Google to digital innovators such as Warby Parker and Peloton. Why? Love. In Winning on Purpose, which grows directly out of NPS, Reichheld argues that the primary purpose of a business should be to enrich the lives of its customers-and the best way to do that is to embrace a rating system that segments customers into Promoters, Passives, and Detractors. NPS illuminates a radically simple idea: prosper by treating people the way you want to be treated. It puts the Golden Rule-and love-at the heart of enduring business success. Across a wide range of industries, the "star" NPS companies consistently deliver higher returns to shareholders. Want to double the stock market returns of an index fund? This book shows you how. But winning on purpose isn't easy. Reichheld explains why most NPS practitioners achieve just a small fraction of the system's full potential and presents the newest thinking and best practices for doing NPS right. He unveils the Earned Growth Rate (EGR): the first reliable measure of what he calls "good profits"-generated when customers come back for more and bring their friends-and argues convincingly that EGR should be included in audited financial statements. Delivering an engaging mix of in-depth business examples and moving personal stories, Reichheld distills and advances the essentials of NPS. Winning on Purpose is the must-read story of the management phenomenon of our time-and your indispensable guide to making NPS the key to your own company's success"--
Includes index.
Keywords: Relationship marketing; Customer loyalty; Consumer satisfaction; Marketing research; Word-of-mouth advertising